SUMBANGAN STUDI AL-QUR'AN BAGI KEILMUAN ISLAM DAN PENDIDIKAN - Nasir, Muhammad Fikri Abdun; Arif, Mahmud (Prodi Ilmu Al-Qur'an dan Tafsir, 2021)
Science and technology, especially modern technology, are changing at a very fast pace, while religious movements are very slow, because religion and technology are not in sync. In the Encyclopedia of Religions and Philosophy, it is explained that Islam is the religion of Allah, and he ordered Allah to teach the principles and rules of the Prophet Muhammad. And commissioned him to convey religion to all mankind by inviting them to accept it. One of the distinguishing features of Islam is its emphasis on knowledge. The Qur'an and Sunnah invite Muslims to seek and acquire knowledge and wisdom, and place great importance on those who are knowledgeable. If we look at the verses in the Qur'an about the command to seek knowledge, then we will find that the commandment is universal, especially in the science called religious knowledge. The Qur'an emphasizes whether knowledge is beneficial or not. The criterion of useful knowledge is to approach the knowledge of the Creator as a form of devotion to Him. The encounter between Muslims and the modern world gave birth to various schools of thought, such as the Salaf school with the motto